Perovskite Light‐Emitting Diodes: Surface‐2D/Bulk‐3D Heterophased Perovskite Nanograins for Long‐Term‐Stable Light‐Emitting Diodes (Adv. Mater. 1/2020). Issue 1 (7th January 2020) - Han, Tae‐Hee; Lee, Jin‐Wook; Choi, Yung Ji; Choi, Chungseok; Tan, Shaun; Lee, Sung‐Joon; Zhao, Yepin; Huang, Yu; Kim, Dongho; Yang, Yang
Abstract : In article number 1905674, Tae‐Hee Han, Yang Yang, and co‐workers suggest an effective solution to mitigate the drawbacks of metal halide perovskites (MHPs) using strategically designed surface‐2D/bulk‐3D heterophased core–shell‐like MHP nanograins for long‐term‐stable light‐emitting diodes.